A proposal to Develop Quality Assurance Standards Based on Electronic learning Technology - Ahmad Albadah; Khalid Alsarayra (University of Science and Technology, Yemen, 2012)
Abstract This research aims at developing criteria for the quality management and assurance. To achieve this objective, the researcher followed the theoretical compositional analytic method, as a means to identify the concept of the total quality management; in order to draw a general framework to develop the TQM and assurance criteria in the higher education institutions. This method explains how would the university administration benefit this modern managerial method as an introduction to reform and develop the educational management . The criteria consisted of the following areas: Leadership, university vision and Mission, Organizational culture, teacher's, educational curricula and program's human and financial resources management and development science research, community service and student's areas: universities higher management, mission of the university, organizational culture, strategic planning, human resources management, on-going improvement, and customer satisfaction. In the light of the results of this study, the researchers recommended that the Arab higher education institutions should activate the quality management system, and commence actual applying thereof, through working toward developing the values and attitudes. This is quite necessary to build a concrete organizational culture to assure the total quality and the implementation processes by all the workers in the universities. Most important of these values are: cooperation, teamwork spirit, time respect and maintenance, eagerness in innovation and renovation, and ongoing improvement. These reflect the extent of interest in quality, through initiation of training centers specially designed for TQM in the universities, which will work toward achieving a high quality level in the group work performance. The researcher further recommends providing a network of interlinked computers containing database, in which all the facts and data are stored, as well as the statistics concerning all the processes in the universities. In addition, it is quite important to support the electronic culture of the workers with these facilities in order to obtain the various and modern information of the different walks of life, especially in the areas of education, teaching and scientific research. Therefore, the investment of the computerized information from this electronic culture in the higher education became very important, especially this culture is characterized by the updating of its data and information, the easy access. Subsequently, they will be utilized for teaching, research and educational activities, which in turn will help in raising the work tone and its quality level in the university